(untitled) (Research, Society and Development, 2020)
The purpose of the study was to identify the socioeconomic and professional profile of owners and food handlers of food trucks in a capital in the south of Brazil, as well as to evaluate the knowledge of these individuals regarding food safety. A total of 119 individuals in Curitiba, Brazil, participated in the study. For data collection, was elaborated a questionnaire about the socio-demographic, professional profile and food safety knowledge, which was filled by the participants during events. The majority of the individuals were owners (75.63%), of the male gender (69.75%), aged between 30 and 44 years-old (56.30%) and with complete/incomplete higher education (55.46%). The participants answered of the questions of food safety correctly (76.63%). There was a significant difference regarding food safety knowledge among the participants related to the level of education (p=0.0054), length of service in the food segment (p=0.0267), and the completion of courses related to the food area (p=0.0016). These results emphasize the need for continuous education and for the development of new strategies for food safety training, in order to improve the knowledge of street food workers.